(untitled) (American Journal of Islam and Society, 1985)
Ibn Khaldun’s theories about perception, logic and knowledge are clearly influenced by Aristotelian thought; however being somewhat ecclectic, he adds, synthesizes and arrives at his own perspective. In addition, however novel Ibn Khaldin’s conclusions may be, there is the underlying awareness of the Source of all knowledge: “Knowledge comes only from Allah, the Strong, the Wise.” His philosophy, guided by the Qur’an and the Sunnah and sparked by his own genius and capacity for speculative thought, sometimes has much in common with Scholastic Realism, and indeed might be classified as Islamic Phenomenology. According to Ibn Khaldun, man is set apart from the lower stages of Allah’s creations by his ability to think. Through this ability and the existence of the soul, he is able to move towards the world of the angels, the essence of which is pure perception and absolute intellection. It is the world of the angels which gives the soul power of perception and motion. Just as the stages are connected upward, so they are connected downward. For example, the soul acquires sense perceptions from the body as preparation for actual intellection and acquires supernatural perceptions from the angel stage for knowledge of a timeless quality. Some scholars have attributed Ibn Khaldun’s description of spheres of existence to Rasa’il Ikhwan As-Safa’ as he was most probably exposed to them via the school of Abu Al-Qasim Maslamah Al-Majriti in Cordova. But , the seventh epistle of the Rasa’il, which deals in detail with the spheres of existence, does not contain Ibn Khaldtin’s concept of upward and downward movement, rather it describes a Platonic view of the soul ...